Factors Associated With Poor Outcome in Patients With Posterior Reversible Encephalopathy Syndrome Admitted to a Tertiary Hospital in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Posterior Reversible Encephalopathy Syndrome (PRES) is a clinical-radiological phenomenon linked to various clinical disorders. There needed to be more studies on the hospital outcome of PRES in Bangladesh. The objective was to investigate the outcome of PRES on different clinical, biochemical, and imaging findings at admission in patients with PRES admitted to a tertiary-level hospital in Bangladesh.Materials and methods: This prospective observational study included 97 cases of PRES from the admitted patients in Chittagong Medical College Hospital. The poor  outcome was defined as an mRS score ³3 or partial symptomatic recovery. Univariate and multivariate analyses were performed to identify the association between different factors and outcomes.Results: The mean age was 23.3±5.6 years (range 18-50 years), 95.9% were women, and most cases (91.8%) had eclampsia. Poor functional outcome was seen in the 4 (4.1%) patients, and incomplete resolution of symptoms was observed in 58.8% (37 out of 94 survived cases) patients at 30-day follow-up. In logistic regression analysis, other than age and severe PRES, extensive oedema was independently associated with the persistence of symptoms after 30 days (OR:10.45, 95% CI:1.29-84.31, p=0.028).Conclusion: The finding of extensive oedema on initial imaging in PRES was associated with poor outcomes.JCMCTA 2023 ; 34 (2) : 73-78